Rs4862705 in the melatonin receptor 1A gene is associated with renal function decline in type 1 diabetes individuals - Daher, Gustavo; Santos-Bezerra, Daniele Pereira; Cavaleiro, Ana Mercedes; Pelaes, Tatiana Souza; Admoni, Sharon Nina; Perez, Ricardo Vessoni; Machado, Cleide Guimarães; Amaral, Fernanda Gaspar do; Cipolla-Neto, José; Correa-Giannella, Maria Lúcia (Frontiers in Endocrinology, 2024)
The pathogenesis of chronic diabetes complications has in oxidative stress one of the major elements and single nucleotide polymorphisms (SNPs) in genes belonging to antioxidant pathways modulate susceptibility to these complications. Considering that melatonin is a powerful antioxidant compound, our aim was to explore, in a longitudinal cohort study of type 1 diabetes (T1D) individuals, the association of microvascular complications and SNPs in the gene encoding melatonin receptor 1A (MTNR1A).Methods: Eight SNPs in MTNR1A were genotyped in 489 T1D individuals. Besides cross-sectional analyses of SNPs with each one of the microvascular complications (distal polyneuropathy, cardiovascular autonomic neuropathy, retinopathy, and diabetic kidney disease), a longitudinal analysis evaluated the associations of SNPs with renal function decline in 411 individuals followed for a median of 8 years. In a subgroup of participants, the association of complications with urinary 6-sulfatoxymelatonin (aMT6s) concentration was investigated. Results: The group of individuals with a renal function decline  5 mL/min/1.73m 2 per year presented a higher frequency of the A allele of rs4862705 in comparison with non-decliners, even after adjustment for confounding variables (OR=1.84, P=0.0046). No other significant associations were found. Conclusions: This is the first study showing an association between a variant in a gene belonging to the melatonin system with renal function decline in the diabetic setting.